Tranexamic Acid in Combination With Vancomycin or Gentamicin Has a Synergistic Effect Against Staphylococci - Benjumea, Antonio; Díaz-Navarro, Marta; Hafian, Rama; Cercenado, Emilia; Sánchez-Somolinos, Mar; Vaquero, Javier; Chana, Francisco; Muñoz, Patricia; Guembe, María (Frontiers in Microbiology, 2022)
Background. Tranexamic acid (TXA) is an antifibrinolytic agent applied in orthopedic surgery and has proven to reduce post-surgery infection rates. We previously showed that TXA also had an additional direct antimicrobial effect against planktonic bacteria. Therefore, we aimed to evaluate whether it has a synergistic effect in combination with antibiotics. Methods. Three ATCC and 7 clinical strains of staphylococci were tested against serial dilutions of vancomycin and gentamicin alone and in combination with TXA at 10 mg/ml and 50 mg/ml. The standardized microtiter plate method was used. Minimal inhibitory concentrations (MIC) were calculated using both standard visualization of well turbidity (the lowest concentration at which a complete absence of well bacterial growth was observed by the researcher) and the automated method (the lowest concentration at which ≥80% reduction of well-bacterial growth was measured using a spectrophotometer). Results. TXA-10 mg/ml reduced the MIC of vancomycin and gentamicin with both the standard method (V: 1-fold dilution, G: 4-fold dilutions) and the automated turbidity method (vancomycin: 8-fold dilutions, gentamicin: 8-fold dilutions). TXA-50 mg/ml reduced the MIC of gentamicin with both the standard turbidity method (6-fold dilutions) and the automated turbidity method (1-fold dilutions). In contrast, for vancomycin, the MIC remained the same using the standard method, and only a 1-fold dilution was reduced using the automated method. Conclusion. Ours was a proof-of-concept study in which we demonstrated that TXA had a synergistic effect when combined with both vancomycin and gentamicin, especially at 10 mg/ml, which is the concentration generally used in clinical practice.